2002
DOI: 10.1177/104063870201400212
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofArcanobacterium(Actinomyces)Pyogenesfrom Cases of Feline Otitis Externa and Canine Cystitis

Abstract: 159Brief Communications of clinical illness and a small focus of infection might only be detectable by postmortem examination.Inflammatory changes within the fetal lung were diffuse, without the abscess formation and necrosis typical of subacute to chronic postnatal R. equi pneumonia. The disseminated nature of the pneumonia was similar to that in a previous report, in which the lesions were suggested to be acute. 2 The presence of R. equi in airways, pulmonary alveolar spaces, and stomach content of both fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 16 publications
1
23
0
3
Order By: Relevance
“…Unlike in livestock, T. pyogenes infections are infrequently described in dogs and cats, probably because this pathogen is not considered to be a normal inhabitant of the mucous membranes of companion animals (Billington et al 2002;Greene 2012). In this study, only one case of pneumonia and another of encephalitis were observed in two dogs, reinforcing that T. pyogenes is an uncommon clinical pathogen among companion animals.…”
Section: Discussionsupporting
confidence: 50%
“…Unlike in livestock, T. pyogenes infections are infrequently described in dogs and cats, probably because this pathogen is not considered to be a normal inhabitant of the mucous membranes of companion animals (Billington et al 2002;Greene 2012). In this study, only one case of pneumonia and another of encephalitis were observed in two dogs, reinforcing that T. pyogenes is an uncommon clinical pathogen among companion animals.…”
Section: Discussionsupporting
confidence: 50%
“…İnku basyon sonrası küçük, iğne ucu büyüklüğünde, β-he moliz yapan, gram pozitif, gram değişken veya pleo morfik görünümlü koloniler şüpheli kabul edildi. Rutin biyokimyasal testler; katalaz ve oksidaz negatif, nitrat redüksiyon, eskülin, jelatin hidroliz, üreaz üretimi, glikoz, maltoz, mannitol, sukroz ve ksiloz fermentasyonu, casein agarda sıvılaşma görünümü, oksidasyon-fermantasyon yönünden incelendi 12,15,17, 21 .…”
Section: Arcanobacterium Pyogenes İzolasyonu Ve İdentifikasyonuunclassified
“…But there are few reports of animal infection caused by this organism [5,6]. The role of A. haemolyticum as a zoonotic disease and its differentiation from the closely related animal pathogen Arcanobacterium pyogenes needs to be defined [7-10]. A. pyogenes is one of the agents of bovine mastitis and is also known to cause pyogenic infections in human [11,12].…”
Section: Introductionmentioning
confidence: 99%